2014
DOI: 10.1007/7854_2014_316
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Biomarkers Informing the Clinical Neuroscience of Schizophrenia: Mismatch Negativity and Prepulse Inhibition of Startle

Abstract: With the growing recognition of the heterogeneity of major brain disorders, and particularly the schizophrenias (SZ), biomarkers are being sought that parse patient groups in ways that can be used to predict treatment response, prognosis, and pathophysiology. A primary focus to date has been to identify biomarkers that predict damage or dysfunction within brain systems in SZ patients, that could then serve as targets for interventions designed to “undo” the causative pathology. After almost 50 years as the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 132 publications
(168 reference statements)
2
36
0
Order By: Relevance
“…Fillman, Sinclair, Fung, Webster, & Shannon Weickert, 2014) both diagnoses can be subsumed within the broad category of psychosis, other diagnostic reconfigurations are also appearing: for example, a meta-analysis by the Cross Disorder Group of the Psychiatric Genetics Consortium (2013) claimed to identify putative genetic influences operating equally with respect to diagnoses of schizophrenia, bipolar disorder, major depression, autism and ADHD. An alternate strategy involves leaving diagnosis largely unquestioned but adopting different bioscientific research strategies: Light & Swerdlow (2014) propose using biomarkers to identify unimpaired neural and cognitive function amongst people given a schizophrenia diagnosis; using drug challenges and practice effects to identify areas of continuing neuroplasticity; and monitoring therapeutic progress in these areas using neurophysiological measures such as prepulse inhibition of startle.…”
Section: Possible Futuresmentioning
confidence: 99%
“…Fillman, Sinclair, Fung, Webster, & Shannon Weickert, 2014) both diagnoses can be subsumed within the broad category of psychosis, other diagnostic reconfigurations are also appearing: for example, a meta-analysis by the Cross Disorder Group of the Psychiatric Genetics Consortium (2013) claimed to identify putative genetic influences operating equally with respect to diagnoses of schizophrenia, bipolar disorder, major depression, autism and ADHD. An alternate strategy involves leaving diagnosis largely unquestioned but adopting different bioscientific research strategies: Light & Swerdlow (2014) propose using biomarkers to identify unimpaired neural and cognitive function amongst people given a schizophrenia diagnosis; using drug challenges and practice effects to identify areas of continuing neuroplasticity; and monitoring therapeutic progress in these areas using neurophysiological measures such as prepulse inhibition of startle.…”
Section: Possible Futuresmentioning
confidence: 99%
“…Although the relative novelty, complexity, and computational demands of independent component analysis have limited its rate of adoption in EEG studies of clinical populations (4,5), we have recently demonstrated that auditory deviance response measures, applied to cortical source activities derived from independent component analysis decomposition, can offer more detailed characterization of SZ group and individual deficits than single-channel measures, accounting for substantial portions of variance in multiple measures of clinical, cognitive, and psychosocial functioning. Source-resolved EEG measures also show promise for use in psychiatric diagnosis (5-7) and in genomic analysis (8,9).…”
Section: See Companion Article On Page 127mentioning
confidence: 99%
“…A strategy for "translating" findings from psychiatric neuroscience to inform treatments in real-world settings involves rational use of evidence about individual subjects obtained from biomarkers to select appropriate treatments (6,8). Given the abundance of evidence of auditory system dysfunction in chronic psychotic illness (e.g., auditory hallucinations, impaired auditory attention and working memory, verbal learning and memory), interventions based on tuning the fidelity and accuracy of auditory information processing may dramatically improve cognition in SZ (10).…”
Section: Eeg Biomarkers For Treatment Selectionmentioning
confidence: 99%
See 2 more Smart Citations